MODAL SOSIAL DALAM PEMBERDAYAAN MASYARAKAT DI DESA PURWOSARI KECAMATAN PURWOSARI KABUPATEN BOJONEGORO - Subagyo, Ridwan Arma (Paradigma, 2021)
Community empowerment is one approach in development that uses social aspects to improve the economic aspects of the community. The social aspect that is commonly used in community empowerment is social capital. In social capital there are elements in the form of values and norms, beliefs, and social networks that are used to achieve empowerment goals. The purpose of this study is to explain the role of the elements of social capital in the process of community empowerment. This research was conducted in Purwosari Village, Purwosari District, Bojonegoro Regency. This study uses a qualitative method with the perspective of Fukuyama’s social capital theory. The subjects in this study were selected purposively which included the village head, head of village welfare, head of RT, head of BUMDes, head of subdistrict empowerment, and members of the empowerment community. Data collection techniques in the form of interviews, observations, and documentation. The data that has been collected was analyzed using the Miles and Huberman model which consists of data reduction, data presentation, and drawing conclusions. The results showed that a value of sincerity and norms of habits help to play a role as a common identity that binds members of the community in forming binding social capital. Trust serves as the basis for building cooperation with other parties in an effort to form a bridging social capital. Social networks play a role in expanding cooperation by involving various parties to form linking social capital. Keywords: elements of social capital, roles, community empowerment